Pengembangan Media Pembelajaran Interaktif Materi Pengenalan Komponen PC pada Siswa Kelas X TKJ SMK Negeri 5 Malang - Suryo Utomo; Hanifah Muslimah Az-Zahra; Wibisono Sukmo Wardhono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
When implementing PPL at State Vocational High School 5 Malang, many students find it difficult to take lessons in the introduction of Personal Computer (PC) components because class X is still unfamiliar with the components of Personal Computer (PC) devices that when they were in middle school they had not learned about any components that are in the Personal Computer because of the limited facilities and infrastructure. So that these deficiencies can be overcome and covered, an Interactive Learning Media (MPI) product is created using the APPED model. This APPED model consists of 5 systematic and logical steps, namely: Initial Analysis and Research, Design, Production, Evaluation, Dissemination. Based on the respondents 'pre tes results, students' completeness is determined by KKM. Completeness of the pre tes scores of two respondents, 70 with the category "complete". But for the other three respondents, the results obtained from the pre tes are still below the KKM so that it falls into the "unfinished" category. For the total number of respondents' pre tes results of 310 with an average rating of 62. While in the post tes results, the five students get a complete score in accordance with the KKM value and above the KKM so that it can be categorized as "complete". From the results above, it can be seen the difference from before and after the respondent is given interactive multimedia-based learning. For the total number of respondents' post tes results of 400 with an average rating of 80. MPI learning proved to be effectively used in learning in class X students of TKJ Negeri 5 Malang.